A Qualitative Study to Explore the Construct of Communication Skills in Middle Childhood - Agnes Indar Etikawati; Ratri Sunar Astuti; Monica Eviandaru Madyaningrum (Journal of Educational, Health and Community Psychology, 2023)
The aim of this study is to explore aspects of children’s communication skills in middle childhood in Indonesia. The study was conducted by using qualitative approach. Data were collected through FGDs with parents of school-aged children and group interviews with fifth-grade students. The FGDs were used to explore parents’ opinions on the expected ways of communicating that children aged 9-11 years or around grades 4 to 6 should be able to perform. In the group interviews, the students were asked to give their opinions on the appropriate ways of communicating, During this process, the children were particularly asked to respond to 14 picture stories that depicted eveyday communication situations. The 14 stories used in the interviews were developed based on a preliminary study that explored the variety of communications children commonly did in their everyday life. All the data collected were analysed by using inductive thematic analysis. The result of the analysis revealed eight themes, including receptive skills, language accuracy, context understanding, openness, assertiveness, self-confidence, social sensitivity, and politeness. This research found two main findings which are themes related to receptive communication skills that emphasized understanding on non-verbal messages and themes related to structure of communication skills that focused on social competence. The themes that represented social competence indicated that both characteristics of individualistic and collectivistic cultures have roles in shaping children’s communication skills.